Oculomotor Behavior Predict Professional Cricket Batting and Bowling Performance - Murray, Nicholas P.; Lawton, Josh; Rider, Patrick; Harris, Nathanial; Hunfalvay, Melissa (Frontiers in Human Neuroscience, 2021)
Importance: A new, shorter version of cricket was introduced recently (Twenty20; T20). Since its inception, T20 cricket has rapidly become a popular and exciting format of the game. However, there is little understanding of factors such as visual motor control that influence expertise. Objective: The purpose of this project is to determine if a series of oculomotor measures can predict batting and bowling performance in professional cricket players. Design: This study used cross-sectional design. Each participant took part in a suite of eye-tracking test to measure oculomotor behavior compared to their performance data. Participants: This study used a convivence sample of fifty-nine male T20 league professional cricket players (30 Bowlers and 29 Batsman). Results: One-way univariate analyses of variance examined the differences in oculomotor behavior between batsman and bowlers. Following a series of a multiple regression analyses were conducted to evaluate how well the visual variables predict bowling and batting performance variables. Results demonstrate that several oculomotor eye tracking measures were good predictors of run performance and strike rate. Likewise, several of the same metrics predicted Runs and Wicket performance for bowlers. Overall, results provided further validation to a growing body of literature supporting the use of eye tracking technology in performance evaluation.